Cyclic sedimentation pattern in Lake Veetka, southeast Estonia: a case study - Saarse, Leili (Geologos, 2015)
A sediment core from Lake Veetka, southeast Estonia, 1077 cm in length and covering 10,500 calibrated years, was examined using loss-on-ignition, grain-size distribution and AMS 14C dating to reconstruct depositional dynamics. The studied core, recovered from the northern part of the lake, shows a cyclic pattern of organic and mineral matter concentration with cycle durations of 100-400 years. Cyclicity is displayed better in sediments laid down between 9,200 and 5,600 cal BP. Within two time windows (5,600-5,100 cal BP and from 1,200 cal BP to the present), sediment composition changed drastically on account of a high and fluctuating mineral matter content, obviously driven by different factors. Little Ice Age cooling is characterised by the highest proportion of mineral matter, and the Medieval Warm Period is typified by high organic matter content. The cyclic change of organic and mineral matter has been related to climate dynamics, most likely an alternation of wet and dry conditions, changes in the water level of the lake and differences in bioproduction